(untitled) (Journal of Asian Development Studies, 2024)
The purpose of this paper was to investigate the impact of tax audit and tax penalty on tax compliance and examine the moderating effect of religiosity on the associations between tax audit and tax penalty with tax compliance in Pakistan. In this study, 400 questionnaires were distributed by using convenience sampling to actual as well as potential taxpayers of Pakistan, after which a total of 247 useable questionnaires were deemed suitable for analysis. Partial least squares structural equation modelling (PLS SEM) was devised using SmartPLS software to validate the measurement model and structural model and the predictive relevance of the study’s model. The findings showed that tax audit and tax penalty were positively associated with the level of tax compliance. They also demonstrated the moderating significant effect of religiosity on the relationship between tax penalty, tax audit and tax compliance. Tax authorities and policymakers in developing majority societies in developing countries and in other South Asian countries, especially in Pakistan may use the results to focus their interest on the formulation of policies founded on the outcomes of the study to strengthen revenue collection. This study extended the deterrence theory in the context of tax compliance by studying tax audit and tax penalty as well as the proposed moderating effect of religiosity in the purview of deterrence theory on tax compliance. The study explored the potential effect of these significant factors of tax compliance among actual as well as potential taxpayers in socio cultural context of Pakistan. Moreover, the suitability for the use of PLS-SEM as a statistical tool in investigating the above-mentioned relationships was also discussed.